Histomorphometry of penile smooth muscle fiber in severe erectile dysfunction - Claro, Joaquim de Almeida; Aboim, José; Andrade, Enrico; Alarcon, Gustavo; Ortiz, Valdemar; Sampaio, Francisco; Srougi, Miguel (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Smooth muscle fiber has fundamental importance in erection. Alterations in its function or quantity may be associated with erectile dysfunction. The study objective was to assess the proportion of penile smooth muscle fiber in patients with severe erectile dysfunction. DESIGN AND SETTING: Clinical study, in the Sexual Dysfunction Group, Universidade Federal de São Paulo (Unifesp), and in the Anatomy Laboratory, Universidade Estadual do Rio de Janeiro (UERJ). METHODS: Twenty patients with severe erectile dysfunction were selected to form two groups of ten patients: one with normal arterial flow (age range: 44 to 78 years) and the other with altered arterial flow (age range: 38 to 67 years). These groups were compared with a group formed by ten cadavers aged 18 to 25 years that were presumed to have been potent. Quantification of the smooth muscle fibers was done by means of an immunohistochemical study. RESULTS: The proportion of smooth muscle fiber found was 41.15% for the control group. The pa- tients with erectile dysfunction and normal arterial flow presented 27.24% and those with altered arterial flow presented 25.74%; 19 patients presented at least one chronic disease or risk factor for erectile dysfunction, with prominence for diabetes mellitus, systemic arterial hyperten- sion and smoking. CONCLUSION: Among patients with severe erectile dysfunction, the arterial flow on its own does not present interference in the proportion of smooth muscle fiber. The diminution of the proportion of smooth muscle fiber may result from chronic diseases and vascular risk factors.